Analysis of the Implementation of the Independent Curriculum at SMPK Yapenthom II Maumere - Riong, Maria Bernadetha Dua; Mole, Paulina Nelce; Yeyen, Yustina Yesisanita; Elizabeth, Agustina; Wea, Kristiana Nathalia; Mele, Lusitania Floribunda (Civiliza Publishing, Indonesia., 2025)
Learning within the new paradigm focuses on strengthening competencies and character development aligned with the values of the Pancasila Student Profile. This study aims to examine the implementation of differentiated physics science learning and the strengthening of the Pancasila Student Profile within the Independent Curriculum at SMPK Yapenthom II Maumere. The research method used was a descriptive qualitative approach, with data collection techniques consisting of teacher interviews and student questionnaires. The results indicate that teachers have systematically implemented differentiated learning through diagnostic assessments and the use of varied and contextual learning strategies and media. The strengthening of the Pancasila Student Profile values is carried out through integration into learning and the Pancasila Student Profile strengthening project (P5). Student responses to differentiated learning and the strengthening of the Pancasila Student Profile were very positive, with percentages of 86.81% and 90.94%, respectively. This study concludes that the practice of differentiated learning and the strengthening of the Pancasila Student Profile at this school have been adaptive, contextual, and student-centered.